Determinants of Hospital Inpatient Costs in the Iranian Elderly: A Micro-costing Analysis - Ebrahim Hazrati; Zahra Meshkani; Saeed Husseini Barghzan; Sanaz Zargar Balaye Jame; Nader Markazi-Moghaddam (Korean Society for Preventive Medicine, 2020)
Objectives Aging is assumed to be accompanied by greater health care expenditures. The objective of this retrospective, bottom-up micro-costing study was to identify and analyze the variables related to increased health care costs for the elderly from the provider's perspective. Methods The analysis included all elderly inpatients who were admitted in 2017 to a hospital in Tehran, Iran. In total, 1288 patients were included. The Mann-Whitney and Kruskal-Wallis tests were used. Results Slightly more than half (51.1%) of patients were males, and 81.9% had a partial recovery. The 60-64 age group had the highest costs. Cancer and joint/orthopedic diseases accounted for the highest proportion of costs, while joint/orthopedic diseases had the highest total costs. The surgery ward had the highest overall cost among the hospital departments, while the intensive care unit had the highest mean cost. No statistically significant relationships were found between inpatient costs and sex or age group, while significant associations (p<0.05) were observed between inpatient costs and the type of ward, length of stay, type of disease, and final status. Regarding final status, costs for patients who died were 3.9 times higher than costs for patients who experienced a partial recovery. Conclusions Sex and age group did not affect hospital costs. Instead, the most important factors associated with costs were type of disease (especially chronic diseases, such as joint and orthopedic conditions), length of stay, final status, and type of ward. Surgical services and medicine were the most important cost items.